1979
DOI: 10.4141/cjas79-017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cecectomy on Digestibility Coefficients and Nitrogen Balance in Ponies

Abstract: WrrrENsEnc, K. 1979

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The current case report proposes the initial use of a low‐bulk diet that focuses on small intestinal absorption, while providing sufficient fibre (1 per cent DM roughage on ideal bodyweight, 26.0 per cent crude fibre on DM basis) to provide colonocytes with an energy source. Since equine caecal amputation is associated with decreased digestibilities of DM, energy and protein (Sauer and others 1979), a 20 per cent increase above maintenance energy requirements (0.139 MJ/kg bodyweight, NRC 2007) was provided to try and maintain current bodyweight after surgery, as well as a protein supply well above NRC (2007) requirement. Having almost lost its entire caecum, the horse was initially fed short‐cut and pelleted roughage (dried short‐cut grass chaff, non‐molassed beet pulp and alfalfa pellets) in order to reduce the physical and mechanical load on the remaining large intestine, as is common practice in diet formulations for horses suffering from right dorsal colitis (Cohen and others 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current case report proposes the initial use of a low‐bulk diet that focuses on small intestinal absorption, while providing sufficient fibre (1 per cent DM roughage on ideal bodyweight, 26.0 per cent crude fibre on DM basis) to provide colonocytes with an energy source. Since equine caecal amputation is associated with decreased digestibilities of DM, energy and protein (Sauer and others 1979), a 20 per cent increase above maintenance energy requirements (0.139 MJ/kg bodyweight, NRC 2007) was provided to try and maintain current bodyweight after surgery, as well as a protein supply well above NRC (2007) requirement. Having almost lost its entire caecum, the horse was initially fed short‐cut and pelleted roughage (dried short‐cut grass chaff, non‐molassed beet pulp and alfalfa pellets) in order to reduce the physical and mechanical load on the remaining large intestine, as is common practice in diet formulations for horses suffering from right dorsal colitis (Cohen and others 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of caecocolic intussusception involves surgery, and, depending on caecal compromise and whether the intussusception can be manually reduced, partial or complete typhlectomy may be indicated (Hubert and others 2000). Although a study by Sauer and others (1979) demonstrated that equine caecal amputation is associated with decreased digestibilities of dry matter (DM), energy, protein, crude and acid‐detergent fibre, there is very little information available about optimal nutritional management after typhlectomy in the horse. This case will therefore report on the nutritional management and follow‐up of a horse that underwent a large partial typhlectomy after caecocolic intussusception.…”
Section: Introductionmentioning
confidence: 99%
“…Partial or complete typhlectomy increases faecal water content and decreases fibre digestibility (Meyer et al 1979;Sauer et al 1979). Partial or complete typhlectomy increases faecal water content and decreases fibre digestibility (Meyer et al 1979;Sauer et al 1979).…”
Section: Anatomical Considerationsmentioning
confidence: 99%
“…A potential mechanism of how the hindgut microbiota improves systemic immunity is by contributing to overall host energy balance (Spiljar et al, 2017). Although N and AA absorption in the hindgut is negligible, and hindgut N disappearance does not contribute to overall N balance (Sauer et al, 1979;Just et al, 1981), hindgut fermentation and volatile fatty acid production can contribute to maintenance energy, improving energy balance Dierick et al, 1989). It is reasonable to consider then that, although hindgut energy utilization can contribute to overall energy balance, a reduced energy and N disappearance, or net appearance as is seen in Bhyo challenge, can negatively contribute to overall energy and N balance and should be explored further.…”
Section: Discussionmentioning
confidence: 99%